Design and development of static testing laboratory set-up for beam-column connection - Brigado, Jayson C. (Animo Repository, 2001)
Abstract. The joints between beams and columns are crucial components in framed structures. In fact, previous studies show that most structural building failures occur not because of any deficiency in analysis of the structure or in the design of its members but because of inadequate attention to the detailing of the connections. Realizing the importance of joint/connection strength, a laboratory apparatus capable of testing single corner beam-column connections under static loading condition was designed, and developed. The apparatus is designed to test specimens of any structural materials such as concrete, steel, and timber in their various beam-to-column connection form with varying dimensions specified herein. It has the prospect to test and investigate primarily, the moment strength of joint connections as well as its shear effect. Researchers can also measure deformations at various points of the specimen subject to mechanical static loading. From these data, the researcher can determine the moment and shear strength of the joint, observe the behavior of the connection during loading up to failure, and estimate for the efficiency of the connection. This thesis also presents a set of experimental procedure and set-ups to guide future researchers on the use of the apparatus in researches on beam-column connections. The testing apparatus was adapted for use in the Light Structures Laboratory of Science and Technology Research Center (DLSU-STRC) on hope that further academic undertakings regarding joint connection techniques and innovations will be pursued.